Clonal Expansion of Biofilm-Forming Salmonella Typhimurium ST34 with Multidrug-Resistance Phenotype in the Southern Coastal Region of China - Li, Wanli; Li, Yinghui; Liu, Yao; Shi, Xiaolu; Jiang, Min; Lin, Yiman; Qiu, Yaqun; Zhang, Qian; Chen, Qiongcheng; Zhou, Li; Sun, Qun; Hu, Qinghua (Frontiers in Microbiology, 2017)
To disclose the antibiotics susceptibility and wide adaptability of commonly occurring genotypes of Salmonella Typhimurium, the antibiotic resistance and biofilm formation of different multilocus-sequence-typing (MLST) types of a collection of 240 S. Typhimurium isolates (33 food and 207 clinical ones) during 2010-2014 in Shenzhen were analyzed. Among these strains, 167 was ST34 (69.58%) and 57 was ST19 (23.75%), respectively. A total of 159 (95.21%) ST34 strains displayed the multidrug resistant phenotype (≥ three classes of antibiotic), whereas only 23 (40.35%) ST19 ones did (P < 0.01). Moreover, a relative high proportion (72.46%) of ST34 isolates was classified as moderate to strong biofilm-producers, while only 15.79% of ST19 (P < 0.01) was. Among the food isolates, more than half (51.52%) were from livestock products, among which 41.18% classified as moderate to strong biofilm-producers. In summary, this study highlights the expansion of S. Typhimurium ST34 of strong biofilm-forming ability and multidrug resistance in the southern coastal region of China. Therefore, monitoring the occurrence of ST34 S. Typhimurium in food sources, especially in livestock products, and taking appropriate measures to control Salmonella spp. infections via decreasing biofilm formation should be addressed.